Systémový přístup v procesu komunitního plánování města Pardubic, příklady dobré praxe pracovní skupiny - Šándorová, Zdenka (Univerzita Pardubice, 2009)
The paper describes and analyses the process of community planning and its phases: general information (The Ministry os Social Affairs); information applied in the process of community planning of social services in Pardubice and specific issues of the „working group“.
Keywords: process of community planning; phases fo community planning; working group of community planning; good practice